أبو عمرو بن العلاء وآراؤه النقدية - ميزاب, اسمهان (جامعة الوادي - University of Eloued, 2017)
تهدف هذه الدراسة إلى تسليط الضوء على بعض المواقف النقدية للعالم اللّغوي والنحوي أبي عمرو بن العلاء، حيث كان مزاجا خاصا، وذهنية خاصة في تاريخ النقد الأدبي، وقد جرّته غيرته على اللغة العربية إلى البحث في مفرداتها وتراكيبها، و أعاريض الشعر فيها بحثا يعتمد على القياس، و وضع القواعد، والموازنات و المقارنات، ولذا فقد خدم نقده العلم، والفن الشعري، وتاريخ الأدب This study aims to focus on some critical viewpoints of the linguist and grammarian Abi Amrou Ibn Ibn Elalaa, which was a special mentality in the history of literary criticism. His ardor on Arabic language led him to searchin its vocabularies and compositions, in addition to its poetry rythma, relying on mensuration, setting rules, symmetries and comparisons. So, its critisism served science and poetical art in addition to history of literature.
مقال
Keywords: أبو عمرو بن العلاء؛ آراء نقدية؛ نحو